A novel phenotype of sporadic Creutzfeldt–Jakob disease. Issue 12 (16th November 2007) - Giaccone, G; Di Fede, G; Mangieri, M; Limido, L; Capobianco, R; Suardi, S; Grisoli, M; Binelli, S; Fociani, P; Bugiani, O; Tagliavini, F
Abstract : An atypical case of sporadic Creutzfeldt–Jakob disease (CJD) is described in a 78-year-old woman homozygous for methionine at codon 129 of the prion protein (PrP) gene. The neuropathological signature was the presence of PrP immunoreactive plaque-like deposits in the cerebral cortex, striatum and thalamus. Western blot analysis showed a profile of the pathological form of PrP (PrP Sc ) previously unrecognised in sporadic CJD, marked by the absence of diglycosylated protease resistant species. These features define a novel neuropathological and molecular CJD phenotype.